Formulasi Sediaan Gel Totol Jerawat Ekstrak Bunga Melati (Jasminum sambac L) - Vina Agustin; Nur Ismiyati; Rini Sulistyawati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Jasmine flowers contain eugenol, linalool, metil salisilat, benzil alkohol and indol. These compounds can inhibit the growth of Propionibacterium acne which cause acne at a concentration of 30% with an inhibition zone of 5.58 mm. This study aims to determine the formulation of jasmine flower extract (Jasminum sambac L) acne gel and evaluate its physical properties. Ethanol extract from jasmine flower was obtained by maceration method using 96% ethanol solvent. The gel formulation was made with 30% and 35% concentrations of jasmine flower ethanol extract, carbomer 940 base, triethanolamine (TEA), methylparaben, propylene glycol and distilled water. Evaluation of physical characteristics include organoleptic test, homogenity, pH test, spreadability and shelf time. The results showed that the formulation of jasmine flower extract acne gel with 35% extract concentration produced good physical properties compared to the gel with 30% concentration. The jasmine flower extract gel made with carbomer 940 base has a distinctive aroma of jasmine flower extract, homogeneous physical properties, an average pH value of 5, and a fairly high viscosity. Jasmine flower extract gel with 30% and 35% concentrations had a spreadability of 3.37 cm and 3.39 cm.